Sebuah Studi pada Wanita Bekerja: Pengaruh Motivational Factors, Purchase Preferences, dan Tendency Towards Health Consciousness terhadap Purchase Intention Green Cosmetics - Catresia Martha Bella; Yessy Artanti (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The study investigated the intention of working women to buy green cosmetic products. In addition, it also analyzes the relationship between motivational factors, purchase preferences, and tendency towards health consciousness on the purchase intention of green cosmetic products. A model was developed to understand the effect of independent variables on the dependent variable. Motivational factors, purchase preferences, and tendency towards health consciousness were considered as independent variables and purchase intention of green cosmetic products as the dependent variable. The survey was conducted using an online questionnaire and collected data from 119 working women. Multiple linear regression in SPSS software was used to analyze the collected data. The results show that motivational factors have no significant effect on the purchase intention of green cosmetics. Meanwhile, purchase preferences and tendency towards health consciousness significantly affect purchase intention of green cosmetics. This study focuses on a group of working women. Future research may involve demographic variables, spending on buying green products, and lifestyle variables. Further research can also use in-depth interviews and focus group discussions on finding out more details regarding the use of green products. The green product is also closely related to the high-involvement product. It becomes interesting to involve it in further research.